K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 8 2022

\(\left(x-1\right)^4=2^4\Leftrightarrow\left[{}\begin{matrix}x-1=2\\x-1=-2\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-1\end{matrix}\right.\)

20 tháng 8 2022

x4=16x4=16

⇔ [16=2416=(2)4[16=2416=(−2)4 

x4=⇒x4= [24(2)4[24(−2)4 

 [x=2x=2

28 tháng 8 2023

\(\left(\dfrac{1}{4}\right)^{2n}=\left(\dfrac{1}{8}\right)^2\)

\(\Rightarrow\left(\dfrac{1}{2}\right)^{2.2n}=\left(\dfrac{1}{2}\right)^{3.2}\)

\(\Rightarrow\left(\dfrac{1}{2}\right)^{4n}=\left(\dfrac{1}{2}\right)^6\)

\(\Rightarrow4n=6\)

\(\Rightarrow n=\dfrac{6}{4}=\dfrac{3}{2}\)

28 tháng 8 2023

n = 3/2

16 tháng 11 2021

mũ 2.

16 tháng 11 2021

2^x.2=8
2^x   =8:2
2^x   =4
2^x   =2^2
=>x  =2

 

4 tháng 6 2021

cá bạn ơi giúp mình với

`#040911`

`(x + 5)^3 = (2x)^3`

`\Rightarrow x + 5 = 2x`

`\Rightarrow x + 5 - 2x = 0`

`\Rightarrow 5 + (x - 2x) = 0`

`\Rightarrow 5 - x = 0`

`\Rightarrow x = 5 - 0`

`\Rightarrow x = 5`

Vậy, `x= 5.`

18 tháng 8 2023

Cảm ơn bạn nha

14 tháng 8 2023

a) 1 + 3 + 5 + ... + 13

= (13 + 1).[(13 - 1) : 2 + 1] : 2

= 14 . 7 : 2

= 49

= 7²

b) 3² + 4² + 12²

= 9 + 16 + 144

= 169

= 13²

24 tháng 4 2019

a) \(2.\left(x+\frac{2}{5}\right)+1\frac{1}{4}=\frac{11}{20}\)

\(2.\left(x+\frac{2}{5}\right)+\frac{5}{4}=\frac{11}{20}\)

\(2.\left(x+\frac{2}{5}\right)=\frac{-7}{10}\)

\(x+\frac{2}{5}=\frac{-7}{20}\)

\(x=\frac{-13}{20}\)

Vậy \(x=\frac{-13}{20}\)

24 tháng 4 2019

b)\(x-1\frac{1}{8}-\frac{2}{3}x-\frac{5}{6}x=75\%\)

  \(\left(x-\frac{2}{3}x-\frac{5}{6}x\right)-\frac{9}{8}=\frac{3}{4}\)

\(\frac{-1}{2}x-\frac{9}{8}=\frac{3}{4}\)

\(\frac{-1}{2}x=\frac{15}{8}\)

\(x=\frac{-15}{4}\)

Vậy \(x=\frac{-15}{4}\)

2 tháng 10 2023

250 : x + 3.5 = 5^2

=> 250:x = 25 - 15 = 10

=> x = 250 : 10 = 25

15 tháng 12 2019

\(4x^2-4x+3\)

\(=\left(4x^2-4x+1\right)+2\)

\(=\left(2x+1\right)^2+2>0\)với mọi x

vậy \(4x^2-4x+3>0\)với mọi x

15 tháng 12 2019

\(4x^2-4x+3=4x^2-4x+1+2=\left(2x-1\right)^2+2\)

Vì \(\left(2x-1\right)^2\ge0\forall x\)\(\Rightarrow4x^2-4x+3\ge2\forall x\)

hay \(4x^2-4x+3>0\forall x\)